Students’ Misconception in Animalia Kingdom - Silvi Puspa Widya Lubis; Putri Dini Meutia; Zamzami Zamzami; Samsuar Samsuar; Syarifah Rahmiza Muzana; Asih Winarty (IAIN Manado, 2023)
Students’ Misconception in Animalia Kingdom. This study aimed to identify the misconception of Grade X students on the concept of animalia kingdom dan to find out the percentage of the students who had misconceptions. This study is quantitative descriptive research. The research instruments used written tests in the form of open-ended multiple-choice tests using the CRI technique. The sample of this research was the students of Grade X IA1 and X IA5 SMA Abulyatama Aceh. The sample was 62 students. Based on the result, it was found that more students “Understand the Concept” than those who experience “Misconceptions,” the percentage of students who experience misconceptions about the concept of animal diversity is 27% and that is in the “moderate” category. The students experienced partial misconception which caused them unable to justify and express inappropriate arguments. This is reflected in several students’ answers who did not provide the reason for their answer choice and some students misinterpreted the reason. In this research, the students usually experience misconceptions caused by associative thinking. The students use false experiences as conceptions, and inaccurate reasons, and draw conclusions based on what they see